The Effect of Red Bean Extract (Phaseolus vulgaris L. sp) on Systemic Lupus Erythematosus (SLE) from Obstetrics and Gynecology Perspective: A Systematic Review - Mukhamad Nooryanto; Chynthea Paramitha Dewi (Asian Journal of Health Research, 2025)
Introduction: Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disease predominantly affecting women of reproductive age, with significant morbidity and mortality. Emerging evidence suggests that diet may modulate disease activity, and red bean (Phaseolus vulgaris L.), rich in bioactive compounds, exhibits potential anti-inflammatory and antioxidant effects.    Material and Methods: A systematic literature review was performed using MeSH terms and relevant keywords related to SLE and red bean extract (Phaseolus vulgaris L.), with searches conducted across PubMed, Scopus, ScienceDirect, ResearchGate, and Google Scholar for studies published between 2013 and November 2023, followed by structured title, abstract, and full-text screening based on predefined criteria.    Results: A total of 696 records were initially identified, of which 423 duplicates were removed. After title and abstract screening, 210 articles were assessed, and 21 full-text articles were reviewed. Eleven studies were excluded due to irrelevant outcomes, inappropriate study design, or language restrictions. Ten studies were included in the qualitative synthesis. The findings suggest that bioactive components of red beans may contribute to reduced inflammatory responses and improved clinical manifestations of SLE. Dietary interventions involving red bean consumption demonstrated potential benefits, particularly for women with SLE who are planning pregnancy.    Conclusion: Nutritional therapy may serve as an effective adjunct in the management of SLE, with red bean–based dietary interventions showing potential to reduce disease activity. Nonetheless, robust experimental and clinical studies are essential to validate their efficacy and inform evidence-based clinical recommendations.